Arab Republic of Egypt - Improving Quality, Equality, and Efficiency in the Education Sector : Fostering a Competent Generation of Youth - World Bank (Washington, DC, 2014)
The purpose of this report is to support the government of the Arab Republic of Egypt in reviewing the status of the pre-university education sector; and in identifying the key challenges it faces as it develops and implements a strategic plan to enhance its base of human capital. The key overarching finding, based primarily on the analyses presented in the second, third and fourth chapters of this report is that while significant progress has been made in providing more educational opportunities to Egyptian citizens, the quality of that educational experience is low and unequally distributed, leading to unequal educational outcomes. While inputs are important to quality, the authors also define quality in terms of specific outcomes that indicate learning at a level necessary to compete in a global marketplace. For instance, international test results, such as the trends in International Mathematics and Science Study (TIMSS), are taken to be a strong indicator of educational outcomes that matter, and quality education is generally assumed to impact those outcomes. In addition, it is also clear that Egypt already spends a large share of its public and private resources (by international comparison) on education and, therefore, further improvements in equality of quality provision need to be financed to a great extent through efficiency gains.